1989
DOI: 10.1016/0014-5793(89)81339-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of rho as a substrate for botulinum toxin C3‐catalyzed ADP‐ribosylation

Abstract: Aplysiu rho and a GTP-binding protein purified from human neutrophil membranes (G& were ADPribosylated by botulinum toxin C, with stoichiometries of 0.8 and 0.6, respectively. Rho and G22K appeared to be different proteins since (i) rho migrated faster on polyacrylamide gels, (ii) unlike Gr2k, rho did not require the presence of cytosol to be ADP-ribosylated, (iii) GzK was not recognized by an anti-rho antiserum, and (iv) antibody 142-24E05 recognized G2rK effectively but only poorly cross reacted with rho. AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…In Fig. 3, the resulting autoradiogram revealed that C3 specifically labeled a species that migrated with an apparent molecular mass of approximately 25 kDa on a 11.25% polyacrylamide gel; this is consistent with previously published reports of the specificity for C3 catalyzed ribosylation of Rho (23,24,37). Lysates from cells cultured in the presence of C3 (lanes 2, 4, 6, 8, 10, and 12) showed a greatly reduced level of 32 P-labeled Rho indicating prior endogenous ADP-ribosylation.…”
Section: C3 Exoenzyme Inhibits Cell Proliferation-given a Role Forsupporting
confidence: 79%
“…In Fig. 3, the resulting autoradiogram revealed that C3 specifically labeled a species that migrated with an apparent molecular mass of approximately 25 kDa on a 11.25% polyacrylamide gel; this is consistent with previously published reports of the specificity for C3 catalyzed ribosylation of Rho (23,24,37). Lysates from cells cultured in the presence of C3 (lanes 2, 4, 6, 8, 10, and 12) showed a greatly reduced level of 32 P-labeled Rho indicating prior endogenous ADP-ribosylation.…”
Section: C3 Exoenzyme Inhibits Cell Proliferation-given a Role Forsupporting
confidence: 79%
“…How ADPribosylation inactivates Rho is not clear. ADP-ribosylation does not affect the interaction of Rho with its upstream regulators such as RhoGAP (29 kDa) (Paterson et al, 1990;Morii et al, 1991), GDP dissociation inhibitor, or stimulator proteins , nor does ADP-ribosylation alter its intrinsic or GAP-stimulated GTPase activities, or its intrinsic GDP/GTP exchange rate (Kikuchi et al, 1988;Quilliam et al, 1989;Paterson et al, 1990). It is therefore likely that ADP-ribosylation affects the interaction of Rho with its effector(s).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the Rho-and Cdc42-activating toxin CNF1 (22, 40) had no effect on ACh release. C3 selectively ADP-ribosylates Rho isoforms at low concentrations (35,36), but also affects Rac at high doses (35,(37)(38)(39). C3 inhibited neurotransmission only when injected at micromolar concentrations into the presynaptic neuron.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, ACh release from presynaptic neurons can be monitored by measuring the amplitude of the evoked transmembrane current in the postsynaptic neuron. To probe the role of Rho-related GTPases in neurotransmitter release, we used ToxB, which specifically glucosylates Rac, Cdc42, and Rho (34); LT, which glucosylates Rac, but has no effect on Rho and Cdc42 (25); and C3, which ADP-ribosylates RhoA, RhoB, RhoC, and Aplysia Rho (35,36) and, under certain circumstances, Rac (35,(37)(38)(39). Glucosylation or ADP-ribosylation in the effector domain of the various Rho, Rac, and Cdc42 isoforms disrupts their interaction with downstream effectors and thereby inactivates the intracellular pathways controlled by these GTPases.…”
Section: Effect Of Clostridial Toxins That Inactivate Rho-related Promentioning
confidence: 99%